PTU-110 Reduction In Serum Sodium (na) In Patients Treated With Terlipressin For Varcieal Bleeding (vb) And Hepatorenal Syndrome (hrs). (9th June 2014) - Sugumaran, A; Lougher, E; Czajkowski, M; Yeoman, A
Abstract : Introduction: Terlipressin is used in the management of VB and HRS. Studies have suggested decrease in Na levels on terlipressin, usually in VB. We set out to report the incidence of fall in serum Na in patients receiving terlipressin for VB or HRS. Methods: Consecutive patients admitted to Gwent Liver Unit who received terlipressin were identified. Main outcome measure was fall in Na level during and up to 5 days post therapy. Results: 60 patients were analysed (32 HRS, 28 VB). Median Na pre-treatment was 133 and 29/60 (48%) had existing hyponatraemia; 16 (27%) had Na <125mmol/l. Na fell in 34/60 patients (57%) and was less likely if baseline hyponatraemia existed (38% VS 74% p = 0.004). A fall of ≥5mmol/l occurred in 23%. Median time to nadir Na was 3 days and time to recovery to pre-treatment Na was 6.5 days. No complications of hyponatremia were observed. Patients with VB were more likely (vs HRS patients) to have any fall in Na or a ≥5mmol/l reduction (68% vs 47% p = 0.1 and 32% vs 16% p = 0.12 respectively) but failed to reach significance. Mortality was 22% overall and a fall in Na was actually associated with reduced mortality –9% vs 34% (p = 0.01). Conclusion: Serum Na falls in >50% receiving terlipressin and a fall ≥5mmol/l noted in 23%. However, no significant complications occurred and a fall in serum Na was actually associated with improved mortality. Patients with VB treated with terlipressin trended towards a greater likelihood of Na reduction versus those with HRS. Disclosure of Interest: None Declared.